Examine the optimal position of controls and display in computer numerical control machines - Muthukumar, K.; Jayan, T. Jishin (Maǧallaẗ al-abḥath al-handasiyyaẗ, 2021)
In engineering industries suffering due to industrial wound and ill health, of the computer numerical control machines operators are in the increasing trend, in the subjective analysis which we carried out for the CNC machine, the operators expressing the discomfort at the neck, upper back, lower back, shoulder, and arm because of working with the keys in the controls and viewing the display. the aim of this examination is to identify the most favourable location of control and display through various muscles that activate while performing in CNC machine operations. we introduce surface Electromyogram (EMG) to determine the muscle activity and deliberate on plane of the body close to respective muscles of an operator. the muscle activity measured for all the twenty subjects, at five different levels to find out the best optimal location for controls and display to establish the findings of the subjective study. though there is no clear trend when all the subjects are aggregated, it is seen that 90 cm-100 cm be the optimum range for the midpoint of the control panel and 143cm-148 cm appears to be the optimum range for the midpoint of the display. since changes in muscle activity are comparatively small for all the six muscles taken for study, however, the effect of cumulative activity borne over a shift, week, month, and year are to be considered. muscle activity may increase in repetitive head/finger movements. these combined effects are to be captured for the ergonomic design of the CNC operator interface.